Interwoven Strands for Refining the Chronology of the Neolithic Tell of Vinča-Belo Brdo, Serbia. Issue 4 (30th August 2016) - Tasić, Nenad; Marić, Miroslav; Filipović, Dragana; Penezić, Kristina; Dunbar, Elaine; Reimer, Paula; Barclay, Alistair; Bayliss, Alex; Gaydarska, Bisserka; Whittle, Alasdair
Abstract: A formally modeled radiocarbon chronology for a new profile through the great Neolithic tell of Vinča-Belo Brdo, Serbia, is the third interwoven strand in refining the chronology of the tell. This now joins models for the whole sequence based on the archive of early excavations, and for the last two known horizons at the top of the settlement mound, investigated in recent decades. In the new deep sounding, Vinča culture occupation from the 52nd century cal BC is slightly later than in the main sequence, probably reflecting the horizontal extension of the tell as it began to grow. The last dated occupation falls in the late 47th–early 46th century cal BC, slightly earlier than in the main sequence, but the top of the profile is affected by the slippage that caused the new excavations. Formal estimates are given for the succession and varying durations of burnt and unburnt houses, and indicate a period in the first part of the 5th millennium without house burning. Overall, the combined results from the three interwoven strands serve to produce a radically enhanced understanding of the temporality of the tell, which builds on, rather than supplants, previous research. We knew previously that Vinča-Belo Brdo was very long-lived, but now we can time that history with much greater precision. We can assert with much greater confidence that its vertical buildup was steady and largely uninterrupted. We have begun, from the work on the top of the tell and in the new deep sounding, to grasp better the fluctuations in house durations from generation to generation, and can now contrast the relative fortunes of unburnt and burnt houses. We can say much more about the timing and tempo of the ending of the tell, and about the possible circumstances in which that took place.